A bibliometric review on 3d concrete printing - de Abreu, Victor Hugo Souza; de Souza, Gabriel Marques (Brazilian Journal of Production Engineering, 2019)
Additive manufacturing is one of the pillars of industry 4.0 and promises to further revolutionize the global market through highly technological and innovative products. An example of additive manufacturing applied to civil construction is 3D concrete printing (3DCP), which allows greater freedom of creation, using bolder geometric shapes, greater quality control and less material waste. In this sense, the present article aimed to carry out a systematic bibliographical review applied to the use of 3D printing in concrete, in view of the increasing popularity on the subject. The results indicated a growing interest in the topic, with an apex in the number of publications in 2018 and the number of citations in 2019. In addition, it was found that the most cited articles in the database deal with the comparison of 3DCP with other processes of additive construction , as well as analyzing its mechanical properties and the incorporation of fibers in its composition.